2019
DOI: 10.1158/1538-7445.am2019-4135
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 4135: Novel dual A2A A2B adenosine receptor antagonists for cancer immunotherapy: in vitro and in vivo characterization

Abstract: Adenosine is important messenger molecule that is involved in signal transmission in central nervous, cardiovascular and immunological systems. The immunosuppressive role of adenosine attract attention of many researchers recently and reversal of that effect is addressed by several different approaches i.e.: inhibition of enzymes that are producing the adenosine in tumor microenvironment like CD39 and CD73 but also the antagonization of adenosine receptors mainly A2A and A2B subtypes. Here we present a novel s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Further results from in vivo testing were disclosed for compound 44. 138 It was somewhat more potent than AB928 in inhibiting CREB phosphorylation in C57BL/6 mice even 12 h after administration (50 mg/kg for compound 44 and 100 mg/kg for AB928). Additionally, compound 44 showed an excellent PK profile (t 1/2 = 3.6 h, C max = 23 000 ng/mL, AUC = 6500 ng•h/mL at 3 mg/kg, po, in mice) and antitumor effects on B16-F10/CT26 tumor models.…”
Section: Oncoimmunological Effects and Binding Modes Of Previouslymentioning
confidence: 94%
See 1 more Smart Citation
“…Further results from in vivo testing were disclosed for compound 44. 138 It was somewhat more potent than AB928 in inhibiting CREB phosphorylation in C57BL/6 mice even 12 h after administration (50 mg/kg for compound 44 and 100 mg/kg for AB928). Additionally, compound 44 showed an excellent PK profile (t 1/2 = 3.6 h, C max = 23 000 ng/mL, AUC = 6500 ng•h/mL at 3 mg/kg, po, in mice) and antitumor effects on B16-F10/CT26 tumor models.…”
Section: Oncoimmunological Effects and Binding Modes Of Previouslymentioning
confidence: 94%
“…Notably, both compounds 43 and 44 exclusively restored the function of monocyte-derived dendritic cells (moDC cells, driven by A 2B R) compared to A 2A R antagonists such as CPI-444. Further results from in vivo testing were disclosed for compound 44 . It was somewhat more potent than AB928 in inhibiting CREB phosphorylation in C57BL/6 mice even 12 h after administration (50 mg/kg for compound 44 and 100 mg/kg for AB928).…”
Section: Small-molecule A2ar Antagonists For Cancer Immunotherapymentioning
confidence: 96%
“…Although several A 2A R antagonists are under clinical trials for cancer immunotherapy, some of them dramatically lose potency when exposed to high level of adenosine. Earlier findings by Jonathan et al have shown that the concentration of adenosine in the extracellular fluid of solid carcinomas may reach a micromolar level (10–100-fold higher than normal concentration) . Generally, the concentration of adenosine in the TME is also higher than that in the pathological conditions of PD .…”
Section: Introductionmentioning
confidence: 99%